Effects of Different Y2O3 Contents on the Microstructure of Ni-Based WC Ceramic Composite Coating by Laser Cladding - JIN Lijun, LIU Zhenzhen (Cailiao Baohu, 2025)
To study the effect of different rare earth Y2O3 contents on the microstructure of laser-cladded Ni-based WC ceramic composite coatings， the Ni-based WC ceramic composite coatings were melted on the surface of 9SiCr using 900W YAG solid laser.The effects of Y2O3 on the structure of the composite coatings were systematically investigated by means of scanning electron microscope (SEM) and X-ray diffraction(XRD).Results showed that the addition of Y2O3 could cause alterations in the relative phase composition ratios within the coating，and Y elements were mainly concentrated at the grain boundary edges.Adding a suitable amount of Y2O3 effectively reduced the coating defects during the cladding process， improved coating densification， promoted more homogeneous microstructural distribution， and significantly refined grain size.When the amount of Y2O3 was 1.5%， the microstructure uniformity of the as-prepared coating was the highest.